1986
DOI: 10.1037/0012-1649.22.1.19
|View full text |Cite
|
Sign up to set email alerts
|

Young children's preference for complementary pairs: Evidence against a shift to a taxonomic preference.

Abstract: The development of conceptual preference for complementary versus taxonomic relationships was examined in children ranging from 3 to 15 years of age. The triads procedure was used with picture pairings familiar to the youngest age group. The data revealed a preference for complementary pairing for all age groups. Studies that have shown a shift from a complementary to a taxonomic conceptual preference in the early school years were reviewed. The utility of conceptualizing the increased use of taxonomic organiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
47
2
7

Year Published

1986
1986
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(62 citation statements)
references
References 10 publications
6
47
2
7
Order By: Relevance
“…Clearly, children have difficulty in identifying the superordinate concepts (see Markman, 1989;Rosch et al, 1976), which have been the taxonomic categories used in most studies, and this is one reason why they have resorted to thematic sorting even when the stimuli were not particularly amenable to it. Greenfield and Scott (1986), for example, found that 3-year-olds could explain 92% of their thematically paired items but only 25% of their taxonomically paired items. Furthermore, children are probably less concerned with consistency in their grouping.…”
Section: Discussionmentioning
confidence: 99%
“…Clearly, children have difficulty in identifying the superordinate concepts (see Markman, 1989;Rosch et al, 1976), which have been the taxonomic categories used in most studies, and this is one reason why they have resorted to thematic sorting even when the stimuli were not particularly amenable to it. Greenfield and Scott (1986), for example, found that 3-year-olds could explain 92% of their thematically paired items but only 25% of their taxonomically paired items. Furthermore, children are probably less concerned with consistency in their grouping.…”
Section: Discussionmentioning
confidence: 99%
“…Thematic categorisation links information on the basis of two variables: complementary role and contiguity in time and space (e.g. chair and table) (Greenfield and Scott 1986;Keil 2008). These studies describe the process of development of the knowledge system characterised by classification and by the hierarchical organisation of concepts and their associations.…”
Section: Introductionmentioning
confidence: 99%
“…According to this view, children first tend to formulate script or thematic categories and then these categories are replaced by taxonomic categories in the period after preschool, including primary school (Greenfield & Scott, 1986;Smiley & Brown, 1979). On the other hand, Nguyen and Murphy (2003) found that taxonomic, script, and evaluative categories start to develop simultaneously in the time between three to six years.…”
mentioning
confidence: 96%
“…Past researchers of conceptual development have focused on the development of children's preference for one or other category (see e.g., Greenfield & Scott, 1986;Smiley & Brown, 1979) or categorical knowledge (see e.g., Nguyen & Murphy, 2003). The issue of how children's categorization skills can be developed has been largely neglected.…”
mentioning
confidence: 99%